Emerging antibody-based products for infectious diseases: Planning for metric ton manufacturing. Issue 2 (29th April 2022) - Whaley, Kevin J; Zeitlin, Larry
ABSTRACT: This review focuses on the emerging monoclonal antibody market for infectious diseases and the metric ton scale manufacturing requirements to meet global demand. Increasing access to existing antibody-based products coupled with the unmet need in infectious disease will likely exceed the current existing global manufacturing capacity. Further, the large numbers of individuals infected during epidemics such as the ongoing COVID-19 pandemic emphasizes the need to plan for metric ton manufacturing of monoclonal antibodies by expanding infrastructure and exploring alternative production systems.